Chinese Travel Behavior in Response to Disastrous Events: The Case of the Japan Earthquake. Issue 2 (2nd April 2016) - Wu, Lingling; Walters, Gabrielle
ABSTRACT: In a bid to identify Chinese travelers that can be relied upon in the event of a significant disaster this paper examines the travel behavior of the Chinese tourism market following the 2011 Japan earthquake. The post-disaster travel behavior of 535 Chinese travelers who had existing plans to travel to Japan at the time of the earthquake is explored to reveal the characteristics of Chinese travelers who would still travel under such circumstances. This paper also identifies the characteristics and concerns of those who canceled their travel indefinitely. Relationships are explored between travel decision and variables such as past travel experience, trip purpose, image perception and demographic background in order to identify dependable tourist markets that can be relied on in the wake of a disaster. Practical implications for destination marketers reliant on this market and seeking to encourage visitation post-disaster are provided.